Inclusion and exclusion strategies for conducting meta-analyses. (4th May 2018) - Swift, Joshua K.; Wampold, Bruce E.
Abstract: Some of the most important decisions that a researcher will make when conducting a meta-analysis are decisions about the search strategies and inclusion/exclusion criteria. Decisions regarding inclusion/exclusion criteria serve to define the scope of a meta-analysis and search strategy decisions can have a large impact on how well the results of a meta-analysis actually represent the existing body of literature. In this article, we provide descriptions and recommendations for performing searches and making inclusion/exclusion decisions. We also provide a review of 65 meta-analyses of psychotherapy versus pharmacotherapy in order to offer frequency data on the use of various search strategies and inclusion/exclusion decisions in the field. Clinical or methodological significance of this article: This article provides a review of and recommendations for inclusion and exclusion strategies when conducting meta-analyses. The recommendations can provide guidance for future meta-analysts. This article also provides information for consumers that may be used to judge the quality of published meta-analyses.